Effect of LED Lighting Illuminance and Correlated Color Temperature on Working Memory - Lee, Chung Won; Kim, Jin Ho (International Journal of Optics, 2020)
This study was conducted to verify how the illuminance and correlated color temperature of LED lighting affect working memory. For this study, an automatic LED lighting device based on a light sensor was developed and used, and the lighting conditions were treated with a total of six conditions (2 × 3): two illuminance conditions (dim: 400 lx, bright: 1,000 lx) and three correlated color temperature conditions (3,000 K, 5,000 K, and 7,000 K). There were 30 participants in the study, and the average age was 21.6 years (Standard deviation = 1.92). Participants were assigned to all six lighting conditions, and the placement order was randomized. For the measurement of working memory, 3-back task was used and the correct responses for 5 minutes were used as a dependent variable. As a result of repeated measures analysis of variance (ANOVA), both illuminance and correlated color temperature were found to be significant variables affecting working memory, and no interaction effect between illuminance and correlated color temperature was found. As a result of the post hoc verification conducted thereafter, the working memory performance in the bright light condition (1,000 lx) was 48.32 (Standard deviation = 15.63) on average, compared to 44.80 (Standard deviation = 15.29) in the relatively dim condition (400 lx). It was found that the condition of bright light was superior in performing working memory compared to relatively dim condition. The working memory performance in the correlated color temperature condition (5,000 K) was 48.32 (Standard deviation = 16.41) on average and higher than that of other color temperature conditions. As a result, working memory performance was the best in 1,000 lx, 5,000 K condition Mean = 53.43 (Standard deviation = 18.38), and 400 lx, 7,000 K condition Mean = 42.73 (Standard deviation = 17.68) showed the worst performance of working memory.